Experimental and numerical investigations on the hybrid dowel and bonding steel plate joints for timber structures. (30th December 2020) - Tang, Liqiu; Yang, Huifeng; Crocetti, Roberto; Liu, Jianzheng; Shi, Benkai; Gustafsson, Per Johan; Liu, Weiqing
Highlights: Monotonic tensile tests of hybrid dowel and bonding steel plate joints. Experimental evaluation on ultimate load carrying capacity and deformation of the joints. Numerical analysis of shear stress distribution and mechanical behaviour of the innovative hybrid joints. Abstract: This paper summarizes the experimental and numerical investigations on an innovative hybrid joint for timber structures. A total of 12 hybrid dowel and bonding steel plate joints divided in four subgroups were investigated. Different parameters such as the presence of self-tapping screws and the surface treatment of the bonding steel plate, were studied. For two subgroups, a vulcanized rubber layer was applied to the bonding steel plate, before gluing it onto the timber surface. Monotonic tensile tests were carried out on the proposed joints and three replicates for each subgroup were constructed. The focus of this research has been on the load-carrying capacity, shear stress and slip stiffness of the proposed joints. Test results showed that the load-carrying capacity of the hybrid joints was much higher than that of similar screw joints. The introduction of the vulcanized rubber layer in the specimens leaded to the slight improvement of load-carrying capacity and the remarkable improvement of maximum slip. The comparisons between numerical and experimental results indicated that the proposed numerical model had a satisfactory agreement with experimental results and could be used to simulate this hybrid joints. The numerical analysis showed that the shear stress was concentrated in edge regions of the bond line for specimens without rubber layer. While the shear stress distribution became much more uniform for specimens with rubber layer. The research results showed that the bonding steel plate joints with 3.0 mm rubber layer were characterized by both high deformability and high load-carrying capacity.